Method of drag polar fragments reading of the airborne recorder in conditions of civil aviation enterprise - Белогузов, В. С.; Мещишен, Д. К. (Proceedings of National Aviation University (archive), 2000)
Presented is the methods of reading fragments of actiual airplane polars from the data of the airborne recorder МСРП-12-96. Considered is the process of its preliminary interpretation on the basis of mean square approximation of table functions changes of flight parameters. Presented are the results of approbation of the given method on the airplane Ah-24